A kind of anti-static ABS composite material based on carbon nanotubes and preparation method thereof
By using carbon nanotubes to prepare composite conductive fillers and modified heat-resistant agents in ABS composites, the problems of insufficient electrostatic, heat resistance and impact resistance of ABS composites are solved, and excellent anti-static, heat resistance and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411865840.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-18
AI Technical Summary
ABS composites are prone to static electricity during use, which limits their application in electronic products and automobile manufacturing fields, and at the same time, their heat resistance and impact resistance are insufficient.
The composite conductive filler based on carbon nanotubes is prepared by ultrasonic treatment and autoclave reaction, and mixed with ABS resin, polycarbonate resin and modified heat-resistant agent, and after melting and extrusion, an antistatic ABS composite material with excellent antistatic, heat-resistant, mechanical properties and impact resistance is prepared.
It realizes the excellent antistatic properties of ABS composites, improves its heat resistance and mechanical properties, enhances impact strength, and meets the application needs in high temperature environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ABS composite materials, and in particular to an anti-static ABS composite material based on carbon nanotubes and a preparation method thereof. Background Art
[0002] ABS resin is made of three chemical substances, butadiene, acrylonitrile and styrene, through polymerization and blending processes. Therefore, ABS resin has the chemical resistance and weather resistance provided by acrylonitrile, the high impact and high rigidity provided by butadiene, and the high fluidity and easy processing of products provided by styrene. ABS resin can be widely used in home appliances, automobile transportation, toy products, daily necessities and other fields, and is currently one of the world's top five general-purpose plastics.
[0003] However, ABS composite materials have good insulation properties, which makes its products prone to static electricity during use, which limits its application in electronic products, automobile manufacturing and other fields. Traditional antistatic ABS composite materials mainly use permanent antistatic agents (expensive) or high content of conductive carbon black, carbon nanotubes, etc. to improve the antistatic properties of composite materials, but single use will result in high production costs. In addition, considering that ABS composite materials may also need to be used in high temperature environments, their heat resistance needs to be improved. Therefore, in response to the above problems, researchers need to develop an antistatic ABS composite material with excellent antistatic properties, heat resistance, impact resistance and mechanical properties. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an anti-static ABS composite material based on carbon nanotubes and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A carbon nanotube-based anti-static ABS composite material comprises the following raw materials in parts by weight: 70-90 parts of ABS resin, 8-15 parts of polycarbonate resin, 5-12 parts of composite conductive filler, 1-3 parts of lubricant, 5-10 parts of modified heat-resistant agent, and 0.2-0.4 parts of antioxidant;
[0007] Further, the lubricant is one of calcium stearate, polyethylene wax or zinc stearate;
[0008] Further, the antioxidant is one of antioxidant 1010, antioxidant 1098 and antioxidant 1076;
[0009] The composite conductive filler is prepared by the following steps:
[0010] Step A1, ultrasonically treating carbon nanotubes (CNTs) in deionized water for 30 minutes, then adding mixed acid, refluxing and stirring at 100° C. for 3-4 hours, centrifuging, washing to neutrality, and drying to obtain pre-treated carbon nanotubes;
[0011] Step A2: Mix ammonium molybdate tetrahydrate in deionized water and adjust the pH to 6-6.5, add reduced glutathione aqueous solution and stir for 10-20 minutes, then add pretreated carbon nanotubes and stir evenly, then transfer to an autoclave, react at 160-200°C for 24 hours, centrifuge, wash and dry to obtain MoS 2 @CNTs(MoS 2 quantum dots loaded with carbon nanotubes);
[0012] Step A3: MoS 2 @CNTs were evenly dispersed in 1,4-dioxane, and then γ-mercaptopropyltriethoxysilane was added. The temperature was raised to 80-90°C and stirred for 4-6 hours. The thiolated MoS 2 @CNTs; then stir nonylphenol polyoxyethylene ether in deionized water, and then add thiolated MoS 2 @CNTs solution and 2-acrylamide-2-methylpropanesulfonic acid, add 0.03 mol / L triethylamine aqueous solution, adjust the system pH to 9-10, raise the temperature to 75-85°C, stir and react for 6-8h, filter, wash and dry to obtain a composite conductive filler;
[0013] Furthermore, in step A1, the amount ratio of carbon nanotubes, deionized water and mixed acid is 0.3-0.5 g: 10 mL: 40 mL, and the mixed acid is prepared by mixing 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1;
[0014] Furthermore, in step A2, the ratio of ammonium molybdate tetrahydrate, deionized water, reduced glutathione aqueous solution and pre-treated carbon nanotubes is 0.5-1.5 g: 80 mL: 20 mL: 1-3 g, and the reduced glutathione aqueous solution is prepared by mixing and stirring reduced glutathione and deionized water in a ratio of 2.5-7.5 g: 20 mL;
[0015] Further, step A3 thiolates MoS 2 @CNTs MoS 2 @The dosage ratio of CNTs, 1,4-dioxane and γ-mercaptopropyltriethoxysilane is 0.5-2g:50mL:0.3-1.5g;
[0016] Furthermore, in step A3, the nonylphenol polyoxyethylene ether, deionized water, thiolated MoS 2The dosage ratio of CNTs solution, 2-acrylamide-2-methylpropanesulfonic acid and triethylamine aqueous solution is 2-3g:100mL:50mL:0.5-2g:10mL. 2 @CNTs solution is made of thiolated MoS 2 @CNTs and deionized water are mixed and stirred in a dosage ratio of 0.5-1.5g:50mL.
[0017] The modified heat-resistant agent is prepared by the following steps:
[0018] Step B1, 2,5-diaminophenol hydrochloride, 4-vinylbenzoic acid and polyphosphoric acid are mixed and stirred, and heated to 100-110° C., reacted for 30 minutes, and then heated to 200° C. for reaction for 2-3 hours, filtered, washed, and collected the product, and then the product was allowed to stand in a 10wt% sodium carbonate aqueous solution for 12 hours, filtered, washed, and dried to obtain a functional monomer;
[0019] Step B2, maleic anhydride is mixed evenly in N,N-dimethylformamide, recorded as solution 1; melamine is mixed evenly in N,N-dimethylformamide, recorded as solution 2; solution 2 is slowly added to solution 1 to react for 1.5-2.5h, anhydrous sodium acetate and hydroquinone are added and stirred evenly, acetic anhydride is added, and the temperature is raised to 45-55°C to react for 2h, cooled, filtered, washed and dried to obtain a maleic anhydride grafted product;
[0020] Step B3, the functional monomer and the maleic anhydride grafted product are mixed and stirred in cyclohexanone, and then transferred to an oil bath pot and heated at 70-80°C for reaction for 30-50 minutes, and then nitrogen is introduced, benzoyl peroxide is added, and the temperature is raised to 100°C for reaction for 3.5-4.5 hours. After cooling, it is precipitated in petroleum ether and acetone in turn, filtered and dried to obtain a modified heat-resistant agent;
[0021] Further, in step B1, the usage ratio of 2,5-p-diaminophenol hydrochloride, 4-vinylbenzoic acid, polyphosphoric acid and sodium carbonate aqueous solution is 0.01-0.03 mol: 0.01-0.03 mol: 8-24 g: 50 mL;
[0022] Further, in step B2, the dosage ratio of solution 1, solution 2, anhydrous sodium acetate, hydroquinone and acetic anhydride is 40 mL: 40 mL: 1-2 g: 0.8-1.6 g: 4-8 mL, the dosage ratio of maleic anhydride and N, N-dimethylformamide in solution 1 is 0.05-0.1 mol: 40 mL, and the dosage ratio of melamine and N, N-dimethylformamide in solution 2 is 0.05-0.1 mol: 40 mL;
[0023] Furthermore, in step B3, the usage ratio of the functional monomer, the maleic anhydride graft, the cyclohexanone, the benzoyl peroxide, the petroleum ether and the acetone is 5-8 g: 3-6 g: 30 mL: 0.4-0.6 g: 50 mL: 50 mL.
[0024] A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps:
[0025] The raw materials are weighed by weight, and ABS resin, polycarbonate resin, composite conductive filler, lubricant, modified heat-resistant agent and antioxidant are mixed and stirred evenly, and then put into a twin-screw extruder, and melted, extruded and granulated to obtain an anti-static ABS composite material based on carbon nanotubes.
[0026] Beneficial effects of the present invention:
[0027] The anti-static ABS composite material prepared by the present invention uses ABS resin as a matrix resin, and polycarbonate resin is added to improve the comprehensive performance of the composite material; carbon nanotubes are used as a substrate, and a composite conductive filler is prepared by modification to improve the conductivity of the matrix, thereby improving the antistatic performance, mechanical properties and impact strength of the matrix; the addition of a modified heat-resistant agent improves the heat resistance of the matrix.
[0028] Composite conductive filler, using mixed acid to pre-treat carbon nanotubes to improve the dispersibility of carbon nanotubes; then using ammonium molybdate tetrahydrate and reduced glutathione as raw materials, MoS 2 Quantum dots, MoS 2 @CNTs; then use silane coupling agent to 2 @CNTs were surface modified to obtain thiolated MoS 2 @CNTs, finally using MoS 2 The thiol groups on the surface of CNTs react with the double bonds in 2-acrylamide-2-methylpropanesulfonic acid to produce a composite conductive filler. The composite conductive filler uses carbon nanotubes and MoS 2 The quantum dots work together to form a conductive network in the matrix, allowing current to flow through it, thereby achieving the conductive function, reducing the surface resistivity of the matrix, and improving the conductivity of the matrix; in addition, the surface of the composite antistatic agent is also grafted with sulfonic acid groups with excellent hydrophilicity, which can adsorb trace moisture in the environment on the surface of the material to form a layer of water film. The water film has a conductive effect, which can help release the surface charge of the material, reduce static electricity accumulation, and further improve the antistatic effect of the matrix. In addition, the carbon nanotubes in the composite conductive filler can also improve the mechanical properties and impact strength of the matrix.
[0029] In the modified heat-resistant agent, 2,5-p-diaminophenol hydrochloride and 4-vinylbenzoic acid are first reacted to generate a functional monomer containing a benzoxazole structure and a terminal double bond structure; then maleic anhydride and melamine are reacted to obtain a maleic anhydride graft containing an imide structure; finally, under the action of an initiator, the functional monomer and the maleic anhydride graft are subjected to a free radical copolymerization reaction to synthesize the modified heat-resistant agent. The modified heat-resistant agent introduces an imide group, a benzoxazole structure, and a triazine structure with excellent heat resistance, and the three act synergistically to improve the heat resistance of the matrix; in addition, the active group (amino group) in the modified heat-resistant agent can also chemically bond with the maleic anhydride structure contained in the ABS resin when it is melted, reducing the degradation of heat resistance due to migration, precipitation, and other problems. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1: The composite conductive filler is prepared by the following steps:
[0032] Step A1, ultrasonically treat 0.3 g of carbon nanotubes in 10 mL of deionized water for 30 min, then add 40 mL of mixed acid (mixed by 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1), reflux and stir at 100° C. for 3 h, centrifuge, wash to neutrality, and dry to obtain pre-treated carbon nanotubes;
[0033] Step A2: 0.5 g of ammonium molybdate tetrahydrate was mixed in 80 mL of deionized water and the pH was adjusted to 6. 20 mL of reduced glutathione aqueous solution was added and stirred for 10 min. 1 g of pretreated carbon nanotubes was added and stirred evenly. The mixture was then transferred to an autoclave and reacted at 160 ° C for 24 h. The mixture was centrifuged, washed and dried to obtain MoS 2 @CNTs, the reduced glutathione aqueous solution is prepared by mixing reduced glutathione and deionized water in a ratio of 2.5 g: 20 mL;
[0034] Step A3: 0.5 g MoS 2 @CNTs were evenly dispersed in 50 mL of 1,4-dioxane, and 0.3 g of γ-mercaptopropyltriethoxysilane was added. The temperature was raised to 80 °C and stirred for 4 h. The thiolated MoS was collected by filtration and washing. 2 @CNTs; 2g of nonylphenol polyoxyethylene ether was stirred evenly in 100mL of deionized water, and then 50mL of thiolated MoS was added under nitrogen.2 @CNTs solution and 0.5g 2-acrylamide-2-methylpropanesulfonic acid, add 10mL, 0.03mol / L triethylamine aqueous solution, adjust the system pH to 9, heat to 75℃, stir and react for 6h, filter, wash and dry to obtain composite conductive filler, thiolated MoS 2 @CNTs solution is made of thiolated MoS 2 @CNTs and deionized water were mixed and stirred in a dosage ratio of 0.5 g:50 mL.
[0035] The modified heat-resistant agent is prepared by the following steps:
[0036] Step B1, 0.01 mol of 2,5-diaminophenol hydrochloride, 0.01 mol of 4-vinylbenzoic acid and 8 g of polyphosphoric acid were mixed and stirred, and heated to 100° C., reacted for 30 min, and then heated to 200° C. for 2 h, filtered, washed, and collected the product, and then the product was allowed to stand in 50 mL, 10 wt% sodium carbonate aqueous solution for 12 h, filtered, washed, and dried to obtain a functional monomer;
[0037] Step B2, 0.05 mol of maleic anhydride was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 1; 0.05 mol of melamine was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 2; 40 mL of solution 2 was slowly added to 40 mL of solution 1 to react for 1.5 h, and then 1 g of anhydrous sodium acetate and 0.8 g of hydroquinone were added and stirred evenly, and then 4 mL of acetic anhydride was added, and the temperature was raised to 45° C. to react for 2 h, cooled, filtered, washed, and dried to obtain a maleic anhydride grafted product;
[0038] Step B3, 5g of the functional monomer and 3g of the maleic anhydride grafted product were mixed and stirred evenly in 30mL of cyclohexanone, then transferred to an oil bath and heated at 70°C for 30min, then nitrogen was introduced, 0.4g of benzoyl peroxide was added, and the temperature was raised to 100°C for 3.5h. After cooling, it was precipitated in 50mL of petroleum ether and 50mL of acetone, filtered and dried to obtain a modified heat-resistant agent.
[0039] Example 2: The composite conductive filler is prepared by the following steps:
[0040] Step A1, ultrasonically treat 0.4 g of carbon nanotubes in 10 mL of deionized water for 30 min, then add 40 mL of mixed acid (mixed by 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1), reflux and stir at 100° C. for 3.5 h, centrifuge, wash to neutrality, and dry to obtain pre-treated carbon nanotubes;
[0041] Step A2: 1 g of ammonium molybdate tetrahydrate was mixed in 80 mL of deionized water and the pH was adjusted to 6.3. 20 mL of reduced glutathione aqueous solution was added and stirred for 15 min. 1-3 g of pretreated carbon nanotubes were added and stirred evenly. The mixture was then transferred to an autoclave and reacted at 180 ° C for 24 h. The mixture was centrifuged, washed and dried to obtain MoS 2 @CNTs, the reduced glutathione aqueous solution is prepared by mixing reduced glutathione and deionized water in a ratio of 5 g: 20 mL;
[0042] Step A3: 1g MoS 2 @CNTs were evenly dispersed in 50 mL of 1,4-dioxane, and 0.9 g of γ-mercaptopropyltriethoxysilane was added. The temperature was raised to 85 °C and stirred for 5 h. The thiolated MoS 2 @CNTs; 2.5 g of nonylphenol polyoxyethylene ether was stirred evenly in 100 mL of deionized water, and then 50 mL of thiolated MoS was added under nitrogen. 2 @CNTs solution and 1g 2-acrylamide-2-methylpropanesulfonic acid, add 10mL, 0.03mol / L triethylamine aqueous solution, adjust the system pH to 9.5, heat to 80℃, stir and react for 7h, filter, wash and dry to obtain composite conductive filler, thiolated MoS 2 @CNTs solution is made of thiolated MoS 2 @CNTs and deionized water were mixed and stirred in a dosage ratio of 1g:50mL.
[0043] The modified heat-resistant agent is prepared by the following steps:
[0044] Step B1, 0.02 mol of 2,5-diaminophenol hydrochloride, 0.02 mol of 4-vinylbenzoic acid and 16 g of polyphosphoric acid were mixed and stirred, and heated to 105° C., reacted for 30 min, and then heated to 200° C. for 2.5 h, filtered, washed, and collected the product, and then the product was allowed to stand in 50 mL, 10 wt% sodium carbonate aqueous solution for 12 h, filtered, washed, and dried to obtain a functional monomer;
[0045] Step B2, 0.075 mol of maleic anhydride was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 1; 0.075 mol of melamine was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 2; 40 mL of solution 2 was slowly added to 40 mL of solution 1 to react for 2 h, and then 1.5 g of anhydrous sodium acetate and 1.2 g of hydroquinone were added and stirred evenly, and then 6 mL of acetic anhydride was added, and the temperature was raised to 50° C. to react for 2 h, cooled, filtered, washed, and dried to obtain a maleic anhydride grafted product;
[0046] Step B3, 6.5g of functional monomer and 4.5g of maleic anhydride grafted product were mixed and stirred evenly in 30mL of cyclohexanone, then transferred to an oil bath and heated at 75°C for 40min, then nitrogen was introduced, 0.5g of benzoyl peroxide was added, and the temperature was raised to 100°C for 4h. After cooling, it was precipitated in 50mL of petroleum ether and 50mL of acetone, filtered and dried to obtain a modified heat-resistant agent.
[0047] Example 3: The composite conductive filler is prepared by the following steps:
[0048] Step A1, ultrasonically treat 0.5 g of carbon nanotubes in 10 mL of deionized water for 30 min, then add 40 mL of mixed acid (mixed by 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:1), reflux and stir at 100° C. for 4 h, centrifuge, wash to neutrality, and dry to obtain pre-treated carbon nanotubes;
[0049] Step A2: 1.5 g of ammonium molybdate tetrahydrate was mixed in 80 mL of deionized water and the pH was adjusted to 6.5. 20 mL of reduced glutathione aqueous solution was added and stirred for 20 min. 1-3 g of pretreated carbon nanotubes were added and stirred evenly. The mixture was then transferred to an autoclave and reacted at 200 ° C for 24 h. The mixture was centrifuged, washed and dried to obtain MoS 2 @CNTs, the reduced glutathione aqueous solution is prepared by mixing reduced glutathione and deionized water in a ratio of 7.5 g:20 mL;
[0050] Step A3: 2g MoS 2 @CNTs were evenly dispersed in 50 mL of 1,4-dioxane, and 1.5 g of γ-mercaptopropyltriethoxysilane was added. The temperature was raised to 90 °C and stirred for 6 h. The thiolated MoS 2 @CNTs; 3 g of nonylphenol polyoxyethylene ether was stirred evenly in 100 mL of deionized water, and then 50 mL of thiolated MoS was added under nitrogen. 2 @CNTs solution and 2g 2-acrylamide-2-methylpropanesulfonic acid, add 10mL, 0.03mol / L triethylamine aqueous solution, adjust the system pH to 10, heat to 85℃, stir and react for 8h, filter, wash and dry to obtain composite conductive filler, thiolated MoS 2 @CNTs solution is made of thiolated MoS 2 @CNTs and deionized water were mixed and stirred in a dosage ratio of 1.5 g:50 mL.
[0051] The modified heat-resistant agent is prepared by the following steps:
[0052] Step B1, 0.03 mol of 2,5-diaminophenol hydrochloride, 0.03 mol of 4-vinylbenzoic acid and 24 g of polyphosphoric acid were mixed and stirred, and heated to 110° C. for reaction for 30 min, and then heated to 200° C. for reaction for 3 h, filtered, washed, and collected the product, and then the product was allowed to stand in 50 mL, 10 wt% sodium carbonate aqueous solution for 12 h, filtered, washed, and dried to obtain a functional monomer;
[0053] Step B2, 0.1 mol of maleic anhydride was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 1; 0.1 mol of melamine was mixed evenly in 40 mL of N, N-dimethylformamide, recorded as solution 2; 40 mL of solution 2 was slowly added to 40 mL of solution 1 to react for 2.5 h, and then 2 g of anhydrous sodium acetate and 1.6 g of hydroquinone were added and stirred evenly, and then 8 mL of acetic anhydride was added, and the temperature was raised to 55 ° C. to react for 2 h, cooled, filtered, washed, and dried to obtain a maleic anhydride grafted product;
[0054] Step B3, 8g of the functional monomer and 6g of the maleic anhydride grafted product were mixed and stirred evenly in 30mL of cyclohexanone, then transferred to an oil bath and heated at 80°C for 30-50min, then nitrogen was introduced, 0.6g of benzoyl peroxide was added, and the temperature was raised to 100°C for 4.5h. After cooling, it was precipitated in 50mL of petroleum ether and 50mL of acetone, filtered and dried to obtain a modified heat-resistant agent.
[0055] Embodiment 4: A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps:
[0056] ABS resin 70 parts, polycarbonate resin 8 parts, composite conductive filler prepared in Example 1 5 parts, calcium stearate 1 part, modified heat-resistant agent prepared in Example 1 5 parts, antioxidant 1010 0.2 parts;
[0057] The raw materials were weighed by weight, and ABS resin, polycarbonate resin, the composite conductive filler prepared in Example 1, calcium stearate, the modified heat-resistant agent prepared in Example 1 and antioxidant 1010 were mixed and stirred evenly, and then put into a twin-screw extruder, and melted, extruded and granulated to obtain an anti-static ABS composite material based on carbon nanotubes.
[0058] Embodiment 5: A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps:
[0059] 80 parts of ABS resin, 12 parts of polycarbonate resin, 9 parts of the composite conductive filler prepared in Example 2, 2 parts of polyethylene wax, 8 parts of the modified heat-resistant agent prepared in Example 2, and 0.3 parts of antioxidant 1098;
[0060] The raw materials are weighed by weight, and ABS resin, polycarbonate resin, the composite conductive filler prepared in Example 2, polyethylene wax, the modified heat-resistant agent prepared in Example 2 and antioxidant 1098 are mixed and stirred evenly, and put into a twin-screw extruder. After melting, extrusion and granulation, an anti-static ABS composite material based on carbon nanotubes is obtained.
[0061] Example 6: A method for preparing an anti-static ABS composite material based on carbon nanotubes comprises the following steps:
[0062] 90 parts of ABS resin, 15 parts of polycarbonate resin, 12 parts of the composite conductive filler prepared in Example 3, 3 parts of zinc stearate, 10 parts of the modified heat-resistant agent prepared in Example 3, and 0.4 parts of antioxidant 1076;
[0063] The raw materials are weighed by weight, and ABS resin, polycarbonate resin, the composite conductive filler prepared in Example 3, zinc stearate, the modified heat-resistant agent prepared in Example 3 and antioxidant 1076 are mixed and stirred evenly, and put into a twin-screw extruder. After melting, extrusion and granulation, an anti-static ABS composite material based on carbon nanotubes is obtained.
[0064] Comparative Example 1: This comparative example is an anti-static ABS composite material, which differs from Example 6 in that carbon black is used instead of the composite conductive filler prepared in Example 3, and the rest are the same.
[0065] Comparative Example 2: This comparative example is an anti-static ABS composite material. The difference from Example 6 is that α-methylstyrene is used instead of the modified heat-resistant agent prepared in Example 3, and the rest is the same.
[0066] The anti-static ABS composite materials prepared in Examples 4-6 and Comparative Examples 1-2 were injection molded into standard-sized specimens by an injection molding machine for performance testing;
[0067] Surface resistivity test: Test surface resistivity according to IEC60093 standard;
[0068] Heat resistance test: Use VicoMetco WKT-VST300D to measure the heat deformation temperature, test conditions: 50℃ / h (5±0.5℃ / 6min);
[0069] Tensile strength test: Use a universal tensile testing machine to test the tensile properties of a 20cm×2cm×0.4cm strip sample;
[0070] Impact strength test: Tested according to DIN ISO 179-1, with a pendulum energy of 4J;
[0071] The test results are shown in Table 1:
[0072]
[0073] It can be seen from Table 1 that after the surface resistivity, heat resistance, tensile strength and impact strength tests, the surface resistivity of the anti-static ABS composite material prepared by the present invention is (1.9×10 6 -4.6×10 6 )Ω, softening point is (126.3-138.1)℃, tensile strength is (45-48)MPa, impact strength is (17.6-18.2)kJ / m 2 , indicating that the composite material has excellent antistatic properties, heat resistance, mechanical strength and impact resistance.
[0074] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they shall all fall within the protection scope of the present invention.
Claims
1. An anti-static ABS composite material based on carbon nanotubes, characterized in that: The invention comprises the following raw materials in parts by weight: 70-90 parts of ABS resin, 8-15 parts of polycarbonate resin, 5-12 parts of composite conductive filler, 1-3 parts of lubricant, 5-10 parts of modified heat-resistant agent, and 0.2-0.4 parts of antioxidant; The composite conductive filler is prepared by the following steps: Step A1, ultrasonically treat the carbon nanotubes in deionized water for 30 minutes, then add a mixed acid, reflux and stir at 100° C. for 3-4 hours, centrifuge, wash until neutral, and dry to obtain pre-treated carbon nanotubes; Step A2, mix ammonium molybdate tetrahydrate in deionized water, adjust the pH to 6-6.5, add reduced glutathione aqueous solution and stir for 10-20 minutes, then add pretreated carbon nanotubes and stir evenly, then transfer to an autoclave, react at 160-200°C for 24 hours, centrifuge, wash and dry to obtain MoS2@CNTs; Step A3, dispersing MoS2@CNTs evenly in 1,4-dioxane, adding γ-mercaptopropyltriethoxysilane, heating to 80-90°C, stirring and reacting for 4-6h, filtering, washing, and collecting the thiolated MoS2@CNTs; Then, nonylphenol polyoxyethylene ether is stirred evenly in deionized water, and then, under nitrogen conditions, thiolated MoS2@CNTs solution and 2-acrylamide-2-methylpropanesulfonic acid are added, and 0.03 mol / L triethylamine aqueous solution is added at the same time, and then the pH of the system is adjusted to 9-10, and the temperature is raised to 75-85°C, and the reaction is stirred for 6-8h, filtered, washed, and dried to obtain a composite conductive filler; The modified heat-resistant agent is prepared by the following steps: Step B1, 2,5-diaminophenol hydrochloride, 4-vinylbenzoic acid and polyphosphoric acid are mixed and stirred, and heated to 100-110° C., reacted for 30 minutes, and then heated to 200° C. for 2-3 hours, filtered, washed, and collected the product, and then the product was allowed to stand in a 10wt% sodium carbonate aqueous solution for 12 hours, filtered, washed, and dried to obtain a functional monomer; Step B2, maleic anhydride is mixed evenly in N,N-dimethylformamide, recorded as solution 1; melamine is mixed evenly in N,N-dimethylformamide, recorded as solution 2; solution 2 is slowly added to solution 1 to react for 1.5-2.5h, anhydrous sodium acetate and hydroquinone are added and stirred evenly, acetic anhydride is added, and the temperature is raised to 45-55°C to react for 2h, cooled, filtered, washed and dried to obtain a maleic anhydride grafted product; Step B3, the functional monomer and the maleic anhydride grafted product are mixed and stirred evenly in cyclohexanone, then transferred to an oil bath pot and heated at 70-80°C for reaction for 30-50min, then nitrogen is introduced, benzoyl peroxide is added, and the temperature is raised to 100°C for reaction for 3.5-4.5h. After cooling, it is precipitated in petroleum ether and acetone in turn, filtered and dried to obtain a modified heat-resistant agent.
2. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step A1, the amount ratio of carbon nanotubes, deionized water and mixed acid is 0.3-0.5 g: 10 mL: 40 mL, and the mixed acid is prepared by mixing 98 wt % concentrated sulfuric acid and 68 wt % concentrated nitric acid in a volume ratio of 3:
1.
3. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step A2, the amount ratio of ammonium molybdate tetrahydrate, deionized water, reduced glutathione aqueous solution and pre-treated carbon nanotubes is 0.5-1.5 g: 80 mL: 20 mL: 1-3 g, and the reduced glutathione aqueous solution is prepared by mixing and stirring reduced glutathione and deionized water in an amount ratio of 2.5-7.5 g: 20 mL.
4. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step A3, the amount ratio of MoS2@CNTs, 1,4-dioxane and γ-mercaptopropyltriethoxysilane in the thiolated MoS2@CNTs is 0.5-2g:50mL:0.3-1.5g, and the amount ratio of nonylphenol polyoxyethylene ether, deionized water, thiolated MoS2@CNTs solution, 2-acrylamide-2-methylpropanesulfonic acid and triethylamine aqueous solution in the composite conductive filler is 2-3g:100mL:50mL:0.5-2g:10mL. The thiolated MoS2@CNTs solution is prepared by mixing and stirring the thiolated MoS2@CNTs and deionized water in a dosage ratio of 0.5-1.5g:50mL.
5. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step B1, the usage ratio of 2,5-p-diaminophenol hydrochloride, 4-vinylbenzoic acid, polyphosphoric acid and sodium carbonate aqueous solution is 0.01-0.03 mol: 0.01-0.03 mol: 8-24 g: 50 mL.
6. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step B2, the dosage ratio of solution 1, solution 2, anhydrous sodium acetate, hydroquinone and acetic anhydride is 40 mL: 40 mL: 1-2 g: 0.8-1.6 g: 4-8 mL, the dosage ratio of maleic anhydride and N, N-dimethylformamide in solution 1 is 0.05-0.1 mol: 40 mL, and the dosage ratio of melamine and N, N-dimethylformamide in solution 2 is 0.05-0.1 mol: 40 mL.
7. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: In step B3, the usage ratio of the functional monomer, maleic anhydride graft, cyclohexanone, benzoyl peroxide, petroleum ether and acetone is 5-8 g: 3-6 g: 30 mL: 0.4-0.6 g: 50 mL: 50 mL.
8. The anti-static ABS composite material based on carbon nanotubes according to claim 1, characterized in that: The lubricant is one of calcium stearate, polyethylene wax or zinc stearate, and the antioxidant is one of antioxidant 1010, antioxidant 1098 and antioxidant 1076.
9. A method for preparing the anti-static ABS composite material based on carbon nanotubes according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials are weighed by weight, and ABS resin, polycarbonate resin, composite conductive filler, lubricant, modified heat-resistant agent and antioxidant are mixed and stirred evenly, and then put into a twin-screw extruder, and melted, extruded and granulated to obtain an anti-static ABS composite material based on carbon nanotubes.
Citation Information
Patent Citations
High-performance vinyl PTC (Positive Temperature Coefficient) composite material and preparation process thereof
CN118772511A
Plastic material for Bluetooth headset shell and preparation method of plastic material
CN119119702A
Manufacturing method of matrix resin containing carbon NANO tube
JP2009138032A